A high-strength steel strand and its application hanging point

By setting an inorganic-organic coating on the surface of high-strength steel strands, and cross-linking of zinc-titanium bimetallic hydroxide layer and photocured polyurethane prepolymers, the problem of easy corrosion in the hanging points of the steel strands is solved, and significant corrosion resistance and service life are improved.

CN115506224BInactive Publication Date: 2025-03-21CHINA CONSTRUCTION INDUSTRIAL & ENERGY ENGINEERING GROUP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211052120.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-29
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing precast concrete structures, the steel stranded lifting points are susceptible to corrosion, resulting in a short service life. The existing enhanced corrosion resistance methods such as coating methods are difficult to achieve long-term protection effects.

Method used

High-strength steel strands are used and an inorganic-organic coating is provided on its surface. The corrosion resistance and self-healing properties are enhanced by cross-linking of the zinc-titanium bimetallic hydroxide layer grown in situ and the photocured polyurethane prepolymer.

Benefits of technology

It significantly improves the corrosion resistance and service life of the steel strand lifting points, ensures long-term protection effect, and further enhances durability through a self-healing mechanism.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115506224B_ABST
    Figure CN115506224B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of precast concrete structures, and in particular to a high-strength steel strand and a suspension point for its application. The suspension point has a simple structure, is easy to manufacture and install, and has high construction efficiency. 2‑ The intercalated zinc-titanium double hydroxide layer serves as an anti-corrosion layer, and a zinc-titanium organic framework is generated in situ on the anti-corrosion layer; self-healing hexamethylene diisocyanate capsules are synthesized; a hydrophobic coating is prepared using 2,6-diaminopyridine as a chain extender and hexamethylene diisocyanate capsules as a monomer. When coated on a surface pretreated substrate, the zinc-titanium organic framework is cross-linked with a polyurethane prepolymer to generate a self-healing polyurethane elastomer based on coordination bonds; dopamine hydrochloride has a self-polymerization effect, and the introduction of fluorinated vinyl polysiloxane greatly improves the hydrophobicity of the steel strand; photocuring is used to improve the bonding force between the inorganic-organic coating and the substrate, thereby improving the various performances of the steel strand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of precast concrete structures, in particular to a high-strength steel strand and a hanging point used therein. Background Art

[0002] With the development of building industrialization, prefabricated components used in buildings are developing towards large-scale. These prefabricated components generally use large amounts of materials, are expensive, and are prone to causing construction inconvenience when flipped, and may even fail to meet the load-bearing requirements.

[0003] In the existing field of prefabricated bridges, heavy-load prefabricated components have a flexible hanging point for steel strands. The ends of the steel strands in the anchoring section use extrusion anchors, and the anchor heads are made using large-scale special extrusion machines. The extrusion construction process has high quality control requirements, complex structure and low efficiency.

[0004] Compared with the steel strands used in inland cities, the steel strands used in precast concrete structures in coastal cities are more susceptible to corrosion, which will seriously endanger the service life of the steel strand suspension points; enhancing the corrosion resistance and durability of construction steel has great economic value and practical significance; the current common method to enhance the corrosion resistance of steel bars is coating, but the single organic coating is easy to age and fall off, making it difficult to achieve long-term protection. Summary of the invention

[0005] The object of the present invention is to provide a high-strength steel strand and a suspension point used therefor, so as to solve the problems in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A high-strength steel strand hanging point comprises a plurality of steel strands, each of which is symmetrically bent in the middle to form a hanging ring, and the ends of the two limbs are pressed into pear-shaped self-anchor heads in a scattered flower shape and anchored into the interior of a precast concrete component.

[0008] Furthermore, the curved arc section in the middle of each steel strand is wrapped with a galvanized casing with a wall thickness of 2-3 mm.

[0009] Furthermore, the bending angles of the steel strand include 120°, 150° and 180°. According to different bending angles, the two limbs of the steel strand are parallel to each other in a U-shape or a V-shape, and can also be cross-processed.

[0010] Furthermore, the number of steel strands is determined by the weight of the prefabricated component borne by a single hanging point and the depth of the anchoring section.

[0011] Furthermore, when multiple steel strands are used, the exposed height of the curved arc section in the middle of each steel strand is kept consistent; the anchoring depth of the embossed anchor heads is kept consistent, or they are staggered at a certain height every other strand; the anchoring depth of the embossed anchor heads is staggered at a certain height every other strand, which will disperse the local anchoring stress of the concrete, reduce the distribution width of the entire hanging point, and avoid conflict with the steel bars of the prefabricated components.

[0012] Furthermore, spiral stirrups or anchoring steel bars may be added to the top of the embossed anchor head.

[0013] Furthermore, when anchoring steel bars are attached to the top of the embossed anchor head, the diameter of the steel bars should be greater than 20 mm, and the anchoring steel bars should be spot welded to the steel strands, and the anchoring steel bars should be spot welded to the prefabricated component steel bars or not spot welded.

[0014] When the reinforcement of prefabricated components is dense, multiple steel strands should be installed one by one when the hanging points are used, and the plane position of the embossed anchor head and the arrangement of the anchor steel bars, including the quantity and position, should be flexibly adjusted, and then the anchor steel bars and the steel strands should be spot welded.

[0015] Furthermore, an anchor plate may be attached to the top of the embossed anchor head, and a positioning hole may be opened on the anchor plate.

[0016] A method for manufacturing a high-strength steel strand hanging point comprises the following steps:

[0017] 1) Cut the steel strands and galvanized casing to the designed length;

[0018] 2) Sleeve the galvanized casing onto the middle section of the steel strand and bend it into shape;

[0019] 3) When adding spiral stirrups or anchor plates, pass both ends of the steel strand through the positioning holes on the spiral stirrups or anchor plates, and press both ends of the steel strand into a pear-shaped self-anchor head;

[0020] 4) When multiple steel strands are used, the steel strands are arranged into groups. When anchor steel bars are added, the anchor steel bars are spot welded to the steel strands;

[0021] 5) Place the hanging point into the prefabricated component reinforcement cage for fixation. When adding anchor reinforcement, spot weld the anchor reinforcement to the reinforcement cage;

[0022] 6) Pour concrete for precast components and complete the hanging points.

[0023] A lightweight embossing anchor machine is used to press the two ends of the steel strand into pear-shaped self-anchor heads with scattered flowers. Only a small top pressure is required when embossing the anchor heads. The production is convenient, the processing efficiency is high, and the construction quality is guaranteed. Even if there are defects, they can be directly observed with the naked eye.

[0024] For lightly loaded components or components with sufficient size for anchoring, only the embossed anchor head structure can be used; for heavily loaded components or components with insufficient size, spiral stirrups, anchor steel bars and other structures can be additionally added, and the anchor steel bars can also be spot welded with the prefabricated component steel bars; the hanging points made by the present invention have strong adaptability, various forms and reliable anchoring.

[0025] In order to avoid the problem that the existing single organic coating is easy to fall off, the present invention arranges an inorganic-organic coating on the surface of the steel strand to improve the corrosion resistance and self-repairing properties of the steel strand, thereby increasing the service life of the hanging point of the steel strand.

[0026] A method for preparing a high-strength steel strand comprises the following steps:

[0027] S1: Wash the base material of the steel strand and dry it for later use;

[0028] S2: Grind the substrate with sandpaper, prepare anti-corrosion liquid, mix the substrate and anti-corrosion liquid, raise the temperature from 25-30℃ to 115-120℃, keep warm for 22-23h, take out and wash with anhydrous ethanol, dry, and obtain in-situ grown CO3 2- an intercalated zinc-titanium double hydroxide layer, i.e., an anti-corrosion layer;

[0029] S3: Pretreatment of the anti-corrosion layer: trimesic acid and N,N-dimethylformamide are mixed and stirred, and polyvinyl pyrrolidone and deionized water are added to obtain a pretreatment solution; the substrate having the anti-corrosion layer is immersed in the pretreatment solution, taken out and dried to obtain a substrate with a surface pretreated surface;

[0030] S4: preparing a hydrophobic coating: in a nitrogen atmosphere, mixing polytetrahydrofuran, hexamethylene diisocyanate capsules, and dibutyltin dilaurate, heating to 80-85°C for 1-2 hours, cooling to 65-70°C, adding 2,6-diaminopyridine and N,N-dimethylformamide, stirring, and drying to obtain a polyurethane prepolymer; mixing a polyurethane prepolymer and chloroform, adding a dopamine hydrochloride solution and a fluorinated vinyl polysiloxane, and stirring to obtain a hydrophobic coating;

[0031] S5: coating a hydrophobic coating on a surface pretreated substrate and irradiating the substrate with light to form a hydrophobic layer, thereby obtaining a high-strength steel strand.

[0032] Furthermore, the working conditions of the illumination are: illumination intensity 1kW / m 2 , lighting time 4-5min.

[0033] Photocuring is used to improve the bonding strength between the inorganic-organic coating and the substrate, thereby improving the various properties of the steel strand. The introduction of fluorinated vinyl polysiloxane effectively improves the photocuring efficiency and the reaction activity of the photocuring.

[0034] Furthermore, the composition of the anti-corrosion liquid is as follows: 50 mL of deionized water is used as a solvent, wherein 0.04 mol / L of zinc nitrate hexahydrate, 0.02 mol / L of titanium tetrachloride, and 0.06 mol / L of urea are contained.

[0035] When urea is used as the alkali source, by controlling the urea concentration, a dense, complete, and less defective CO3 2- The intercalated zinc-titanium double hydroxide layer achieves chemical repulsion and physical barrier to chloride ions, demonstrating good corrosion resistance and application potential in rust prevention of construction steel.

[0036] Furthermore, in the pretreatment solution, the mass ratio of trimesic acid to polyvinyl pyrrolidone is 0.1:2.

[0037] In the anti-corrosion layer, there is CO3 2- The intercalated zinc-titanium double hydroxide layer is treated with trimesic acid and polyvinyl pyrrolidone, that is, a zinc-titanium organic framework is in situ generated on the anti-corrosion layer, thereby enhancing the bonding force with the subsequent organic coating, thereby enhancing the corrosion resistance of the steel strand surface.

[0038] Furthermore, the preparation of the dopamine hydrochloride solution includes the following steps: tris(hydroxymethyl)aminomethane, dopamine hydrochloride and deionized water are mixed and stirred, and the pH is adjusted to 8.4-8.7 to obtain a dopamine hydrochloride solution.

[0039] Furthermore, the preparation of fluorinated vinyl polysiloxane includes the following steps: under a nitrogen atmosphere, octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane, and tetramethyltetraenylcyclotetrasiloxane are mixed, and the mixture is heated to 85-90° C. and kept warm for 20-30 minutes; the mixture is heated to 105-110° C., an aqueous solution of tetramethylammonium hydroxide is added, deionized water is added, and the mixture is kept warm for 2-3 hours; the mixture is heated to 145-150° C. and kept warm for 2 hours, and the pressure is reduced for 3 hours to obtain fluorinated vinyl polysiloxane.

[0040] Further, the preparation of hexamethylene diisocyanate capsules comprises the following steps:

[0041] Mix urea and deionized water, add resorcinol, ammonium chloride, deionized water, add sodium dodecylbenzene sulfonate solution, stir for 30-40 minutes, add hexamethylene diisocyanate, continue stirring for 20-30 minutes, add 1-2 drops of 1-octanol and formaldehyde, ultrasonically disperse in an ice bath environment for 20-30 minutes, heat to 55-60°C and keep warm for 3-4 hours, wash with ethanol and petroleum ether for 5-10 times, filter and dry to obtain hexamethylene diisocyanate capsules.

[0042] The synthesized hexamethylene diisocyanate capsules with a certain mechanical strength are equivalent to barrier functional fillers, which will prolong the invasion path of corrosive media into the substrate and produce a synergistic enhancement effect of anti-corrosion performance; on the other hand, the self-healing microcapsules on the surface of the coating are damaged at the initial stage of immersion, and the hexamethylene diisocyanate self-healing liquid penetrates into the inherent microscopic pores formed by solvent evaporation in the anti-corrosion coating due to capillary action, thereby improving the corrosion resistance of the coating.

[0043] When there are too few hexamethylene diisocyanate capsules, the improvement in the corrosion resistance and self-healing synergistic effect of the coating is not obvious; while excessive addition will cause agglomeration inside the hexamethylene diisocyanate capsules, which in turn affects the density and barrier ability of the coating, causing a sharp drop in the adhesion of the coating, and having a negative impact on the anti-corrosion performance of the coating.

[0044] Beneficial effects of the present invention:

[0045] The present invention provides a high-strength steel strand and a hanging point used therein. An inorganic-organic coating is arranged on the surface of the steel strand to improve the corrosion resistance and self-repairing properties of the steel strand. During the preparation of the hanging point, the embossing equipment is light and compact. The manufactured hanging points have various forms, strong adaptability and reliable anchoring, thereby improving the service life.

[0046] In-situ generation of CO3 2- The intercalated zinc-titanium double hydroxide layer improves the corrosion resistance of the steel strand; the hydrophobic coating adopts photocuring to improve the bonding force between the inorganic-organic coating and the substrate, thereby improving the various properties of the steel strand, and the introduction of fluorinated vinyl polysiloxane effectively improves the photocuring efficiency and the reaction activity of the photocuring.

[0047] The anti-corrosion layer is treated with trimesic acid and polyvinyl pyrrolidone, that is, a zinc-titanium organic framework is generated in situ on the anti-corrosion layer, thereby enhancing the bonding force with the subsequent organic coating, thereby enhancing the corrosion resistance of the steel strand surface.

[0048] A polyurethane prepolymer was prepared using 2,6-diaminopyridine as a chain extender and hexamethylene diisocyanate capsules as monomers. When the hydrophobic coating was coated on the surface-pretreated substrate, the zinc-titanium organic framework was cross-linked with the polyurethane prepolymer to generate a self-healing polyurethane elastomer based on coordination bonds. Dopamine hydrochloride has a self-polymerization effect, and the introduction of fluorinated vinyl polysiloxane greatly improves the hydrophobicity of the steel strand.

[0049] By optimizing the interfacial polymerization method, the hexamethylene diisocyanate repair agent was encapsulated in the resin capsule wall, and low-particle-size hexamethylene diisocyanate capsules with certain self-healing properties were synthesized; when scratches and other crack defects appear on the coating, the hexamethylene diisocyanate capsules play a synergistic role in the self-healing of the polyurethane in the coating. The self-healing solution in the hexamethylene diisocyanate capsules seeps into the scratch defects in large quantities, and polymerization of the polyurethane self-healing substance occurs in the water environment, effectively preventing the development of local corrosion reactions and producing a synergistic coating self-healing effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a schematic diagram of a high-strength steel strand hanging point in Example 1;

[0051] Figure 2 for Figure 1 AA section view;

[0052] Figure 3 A schematic diagram of a high-strength steel strand hanging point in Example 2;

[0053] Figure 4 for Figure 3 BB cross-section diagram;

[0054] Figure 5 This is a schematic diagram of a high-strength steel strand hanging point in Example 3;

[0055] Figure 6 for Figure 5 CC cross-section diagram.

[0056] Figure 7 This is a schematic diagram of a high-strength steel strand hanging point in Example 4;

[0057] Figure 8 for Figure 7 DD cross-section diagram.

[0058] Fig. 9 A schematic diagram of a high-strength steel strand hanging point in Example 5;

[0059] Fig.10 for Fig. 9 EE profile diagram;

[0060] In the figure, 1 is embossed anchor head, 2 is galvanized casing, 3 is steel strand, 4 is spiral stirrup, 5 is anchor steel bar, and 6 is anchor plate. DETAILED DESCRIPTION

[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, back, etc., the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0063] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0064] Example 1

[0065] A method for preparing a high-strength steel strand comprises the following steps:

[0066] S1: Wash the base material of the steel strand and dry it for later use;

[0067] S2: The substrate was polished with 500# and 1000# SiC sandpapers in turn, and then an anti-corrosion liquid was prepared. The substrate and the anti-corrosion liquid were mixed, and the temperature was raised from 25°C to 115°C at 0.5°C / min, and kept warm for 22 hours. The substrate was taken out and washed with anhydrous ethanol and dried to obtain the in-situ grown CO3 2- an intercalated zinc-titanium double hydroxide layer, i.e., an anti-corrosion layer;

[0068] The composition of the anti-corrosion liquid is as follows: 50 mL of deionized water as solvent, wherein 0.04 mol / L of zinc nitrate hexahydrate, 0.02 mol / L of titanium tetrachloride, and 0.06 mol / L of urea;

[0069] S3: Pretreatment of the anti-corrosion layer: 0.1 g of trimesic acid and 50 mL of N,N-dimethylformamide were mixed and stirred, and 2 g of polyvinyl pyrrolidone and 50 mL of deionized water were added to obtain a pretreatment solution; the substrate with the anti-corrosion layer was immersed in the pretreatment solution for 10 minutes, and dried to obtain a substrate with a surface pretreated surface;

[0070] S4: preparing a hydrophobic coating: in a nitrogen atmosphere, 5 mL of polytetrahydrofuran, 1 g of hexamethylene diisocyanate capsules, and 0.01 g of dibutyltin dilaurate were mixed, the temperature was raised to 80°C and kept for 2 h, the temperature was lowered to 65°C, 0.2 g of 2,6-diaminopyridine and 10 mL of N,N-dimethylformamide were added, the mixture was stirred for 5 min, and dried to obtain a polyurethane prepolymer;

[0071] The preparation of hexamethylene diisocyanate capsules comprises the following steps:

[0072] 5 g of urea and 50 mL of deionized water were mixed and stirred, 0.3 g of resorcinol, 0.3 g of ammonium chloride, and 100 mL of deionized water were added, 4.5 mL of sodium dodecylbenzenesulfonate solution was added, and the mixture was stirred for 30 min. 3 mL of hexamethylene diisocyanate was added, and the mixture was stirred for 20 min. 1 drop of 1-octanol and 3.2 g of formaldehyde were added, and the mixture was ultrasonically dispersed in an ice bath environment for 20 min. The mixture was heated to 55 ° C and kept warm for 4 h. The mixture was washed with ethanol and petroleum ether for 5 times, filtered, and dried to obtain hexamethylene diisocyanate capsules.

[0073] 1 g of polyurethane prepolymer and 9 mL of chloroform were mixed, and 5 mL of 2 g / L dopamine hydrochloride solution and 0.1 g of fluorinated vinyl polysiloxane were added and stirred for 5 min to obtain a hydrophobic coating;

[0074] The preparation of dopamine hydrochloride solution comprises the following steps: 10 mmol tris(hydroxymethyl)aminomethane, 0.3 g dopamine hydrochloride and 150 mL deionized water are mixed and stirred, and the pH is adjusted to 8.4 to obtain a dopamine hydrochloride solution;

[0075] The preparation of fluorinated vinyl polysiloxane comprises the following steps: in a nitrogen atmosphere, 0.24 g of octamethylcyclotetrasiloxane, 0.5 g of trifluoropropyltrimethylcyclotrisiloxane and 0.28 g of tetramethyltetraenylcyclotetrasiloxane are mixed, and the mixture is heated to 85° C. and kept warm for 30 min; the mixture is heated to 105° C., an aqueous solution of tetramethylammonium hydroxide having a total monomer mass fraction of 1.1 / 10,000 is added, 7 mg of deionized water is added, the mixture is kept warm for 2 h, the mixture is heated to 145° C. and kept warm for 2 h, and the mixture is decompressed for 3 h to obtain fluorinated vinyl polysiloxane;

[0076] S5: Apply the hydrophobic coating to the surface pretreated substrate at 150 μm at 1 kW / m 2 After irradiation for 4 minutes at a high light intensity, a hydrophobic layer is formed to obtain a high-strength steel strand.

[0077] A high-strength steel strand hanging point, such as Figure 1-2As shown, it includes an embossed anchor head 1, a galvanized sleeve 2, a steel strand 3 and a spiral stirrup 4; five steel strands 3 are used, the middle part of the steel strand 3 is symmetrically bent 180° to form a hanging ring, the arc section is wrapped with a galvanized sleeve 2, and the wall thickness of the galvanized sleeve 2 is 2mm; the two limbs of the steel strand 3 are parallel U-shaped, and the ends of the two limbs are pressed into a scattered flower-like pear-shaped anchor head 1, and a spiral stirrup 4 is attached to the top of the embossed anchor head 1; the embossed anchor heads 1 are anchored in the interior of the precast concrete component at the same depth.

[0078] Example 2

[0079] A method for preparing a high-strength steel strand comprises the following steps:

[0080] S1: Wash the base material of the steel strand and dry it for later use;

[0081] S2: The substrate was polished with 500# and 1000# SiC sandpapers in turn, and then an anti-corrosion liquid was prepared. The substrate and the anti-corrosion liquid were mixed, and the temperature was raised from 28°C to 118°C at 0.5°C / min, and kept warm for 22.5h. The substrate was taken out and washed with anhydrous ethanol and dried to obtain the in-situ grown CO3 2- an intercalated zinc-titanium double hydroxide layer, i.e., an anti-corrosion layer;

[0082] The composition of the anti-corrosion liquid is as follows: 50 mL of deionized water as solvent, wherein 0.04 mol / L of zinc nitrate hexahydrate, 0.02 mol / L of titanium tetrachloride, and 0.06 mol / L of urea;

[0083] S3: Pretreatment of the anti-corrosion layer: 0.1 g of trimesic acid and 50 mL of N,N-dimethylformamide were mixed and stirred, and 2 g of polyvinyl pyrrolidone and 50 mL of deionized water were added to obtain a pretreatment solution; the substrate with the anti-corrosion layer was immersed in the pretreatment solution for 12 minutes, and dried to obtain a substrate with a surface pretreated surface;

[0084] S4: Preparation of hydrophobic coating:

[0085] In a nitrogen atmosphere, 5 mL of polytetrahydrofuran, 1 g of hexamethylene diisocyanate capsules, and 0.01 g of dibutyltin dilaurate were mixed, heated to 82 °C and kept for 1.5 h, cooled to 68 °C, 0.2 g of 2,6-diaminopyridine and 10 mL of N,N-dimethylformamide were added, stirred for 8 min, and dried to obtain a polyurethane prepolymer;

[0086] The preparation of hexamethylene diisocyanate capsules comprises the following steps:

[0087] 5 g of urea and 50 mL of deionized water were mixed and stirred, 0.3 g of resorcinol, 0.3 g of ammonium chloride, and 100 mL of deionized water were added, 4.5 mL of sodium dodecylbenzene sulfonate solution was added, and the mixture was stirred for 35 min. 3 mL of hexamethylene diisocyanate was added, and the mixture was stirred for 25 min. 1 drop of 1-octanol and 3.2 g of formaldehyde were added, and the mixture was ultrasonically dispersed in an ice bath environment for 25 min. The mixture was heated to 58 ° C and kept warm for 3.5 h. The mixture was washed with ethanol and petroleum ether for 8 times, filtered, and dried to obtain hexamethylene diisocyanate capsules.

[0088] 1 g of polyurethane prepolymer and 9 mL of chloroform were mixed, and 5 mL of 2 g / L dopamine hydrochloride solution and 0.1 g of fluorinated vinyl polysiloxane were added and stirred for 8 min to obtain a hydrophobic coating;

[0089] The preparation of dopamine hydrochloride solution comprises the following steps: 10 mmol tris(hydroxymethyl)aminomethane, 0.3 g dopamine hydrochloride and 150 mL deionized water are mixed and stirred, and the pH is adjusted to 8.5 to obtain a dopamine hydrochloride solution;

[0090] The preparation of fluorinated vinyl polysiloxane comprises the following steps: in a nitrogen atmosphere, 0.24 g of octamethylcyclotetrasiloxane, 0.5 g of trifluoropropyltrimethylcyclotrisiloxane and 0.28 g of tetramethyltetraenylcyclotetrasiloxane are mixed, and the mixture is heated to 85-90° C. and kept warm for 25 min; the mixture is heated to 108° C., an aqueous solution of tetramethylammonium hydroxide having a total monomer mass fraction of 1.1 / 10,000 is added, 7 mg of deionized water is added, the mixture is kept warm for 2.5 h, the mixture is heated to 148° C. and kept warm for 2 h, and the mixture is decompressed for 3 h to obtain fluorinated vinyl polysiloxane;

[0091] S5: Apply the hydrophobic coating to the surface pretreated substrate at 150 μm at 1 kW / m 2 After irradiation for 4.5 min at a light intensity of 1:1, a hydrophobic layer is formed to obtain a high-strength steel strand.

[0092] A high-strength steel strand hanging point, such as Figure 3-4 As shown, it includes an embossed anchor head 1, a galvanized sleeve 2, a steel strand 3 and an anchoring steel bar 5; five steel strands 3 are used, the middle part of the steel strand 3 is symmetrically bent 180° to form a hanging ring, the arc section is wrapped with a galvanized sleeve 2, and the wall thickness of the galvanized sleeve 2 is 2mm; the two limbs of the steel strand 3 are parallel to each other in a U shape, and the ends of the two limbs are pressed into a scattered flower-like pear-shaped anchor head 1, and an anchoring steel bar 5 is attached to the top of the embossed anchor head 1; the anchoring steel bar 5 is spot welded to the steel strand 3; the embossed anchor head 1 is anchored into the interior of the precast concrete component and arranged at a certain height with each root staggered.

[0093] Example 3

[0094] A method for preparing a high-strength steel strand comprises the following steps:

[0095] S1: Wash the base material of the steel strand and dry it for later use;

[0096] S2: The substrate was polished with 500# and 1000# SiC sandpapers in turn, and then an anti-corrosion liquid was prepared. The substrate and the anti-corrosion liquid were mixed, and the temperature was raised from 30°C to 120°C at 0.5°C / min, and kept warm for 23 hours. The substrate was taken out and washed with anhydrous ethanol and dried to obtain the in-situ grown CO3 2- an intercalated zinc-titanium double hydroxide layer, i.e., an anti-corrosion layer;

[0097] The composition of the anti-corrosion liquid is as follows: 50 mL of deionized water as solvent, wherein 0.04 mol / L of zinc nitrate hexahydrate, 0.02 mol / L of titanium tetrachloride, and 0.06 mol / L of urea;

[0098] S3: Pretreatment of the anti-corrosion layer: 0.1 g of trimesic acid and 50 mL of N,N-dimethylformamide were mixed and stirred, and 2 g of polyvinyl pyrrolidone and 50 mL of deionized water were added to obtain a pretreatment solution; the substrate with the anti-corrosion layer was immersed in the pretreatment solution for 15 minutes, and dried to obtain a substrate with a surface pretreated surface;

[0099] S4: preparing a hydrophobic coating: in a nitrogen atmosphere, 5 mL of polytetrahydrofuran, 1 g of hexamethylene diisocyanate capsules, and 0.01 g of dibutyltin dilaurate were mixed, the temperature was raised to 85°C and kept for 1 h, the temperature was lowered to 70°C, 0.2 g of 2,6-diaminopyridine and 10 mL of N,N-dimethylformamide were added, the mixture was stirred for 10 min, and dried to obtain a polyurethane prepolymer;

[0100] The preparation of hexamethylene diisocyanate capsules comprises the following steps:

[0101] 5 g of urea and 50 mL of deionized water were mixed and stirred, 0.3 g of resorcinol, 0.3 g of ammonium chloride, and 100 mL of deionized water were added, 4.5 mL of sodium dodecylbenzenesulfonate solution was added, and the mixture was stirred for 40 min. 3 mL of hexamethylene diisocyanate was added, and the mixture was stirred for 30 min. 2 drops of 1-octanol and 3.2 g of formaldehyde were added, and the mixture was ultrasonically dispersed in an ice bath environment for 30 min. The mixture was heated to 60 ° C and kept warm for 3 h. The mixture was washed with ethanol and petroleum ether for 10 times, filtered, and dried to obtain hexamethylene diisocyanate capsules.

[0102] 1 g of polyurethane prepolymer and 9 mL of chloroform were mixed, and 5 mL of 2 g / L dopamine hydrochloride solution and 0.1 g of fluorinated vinyl polysiloxane were added and stirred for 10 min to obtain a hydrophobic coating;

[0103] The preparation of dopamine hydrochloride solution comprises the following steps: 10 mmol tris(hydroxymethyl)aminomethane, 0.3 g dopamine hydrochloride and 150 mL deionized water are mixed and stirred, and the pH is adjusted to 8.7 to obtain a dopamine hydrochloride solution;

[0104] The preparation of fluorinated vinyl polysiloxane comprises the following steps: in a nitrogen atmosphere, 0.24 g of octamethylcyclotetrasiloxane, 0.5 g of trifluoropropyltrimethylcyclotrisiloxane and 0.28 g of tetramethyltetraenylcyclotetrasiloxane are mixed, and the mixture is heated to 90° C. and kept warm for 20 min; the mixture is heated to 110° C., an aqueous solution of tetramethylammonium hydroxide having a total monomer mass fraction of 1.1 / 10,000 is added, 7 mg of deionized water is added, the mixture is kept warm for 3 h, the mixture is heated to 150° C. and kept warm for 2 h, and the mixture is decompressed for 3 h to obtain fluorinated vinyl polysiloxane;

[0105] S5: Apply the hydrophobic coating to the surface pretreated substrate at 150 μm at 1 kW / m 2 After irradiation for 5 minutes at a high light intensity, a hydrophobic layer is formed to obtain a high-strength steel strand.

[0106] A high-strength steel strand hanging point, such as Figure 5-6 As shown, it includes an embossed anchor head 1, a galvanized sleeve 2, a steel strand 3 and an anchor steel bar 5; five steel strands 3 are used, the middle part of the steel strand 3 is symmetrically bent 150° to form a lifting ring, the arc section is wrapped with a galvanized sleeve 2, and the wall thickness of the galvanized sleeve 2 is 3mm; the two limbs of the steel strand 3 are V-shaped, and the ends of the two limbs are pressed into a scattered flower-like pear shape from the anchor head 1, and an anchor steel bar 5 is attached to the top of the embossed anchor head 1; the anchor steel bar 5 is spot welded to the steel strand 3; the embossed anchor head 1 is anchored into the interior of the precast concrete component at the same depth.

[0107] Example 4

[0108] A high-strength steel strand prepared in the same manner as in Example 3;

[0109] A high-strength steel strand hanging point, such as Figure 7-8 As shown, it includes an embossed anchor head 1, a galvanized sleeve 2, a steel strand 3 and an anchor steel bar 5; five steel strands 3 are used, the middle part of the steel strand 3 is symmetrically bent 150° to form a hanging ring, the arc section is wrapped with a galvanized sleeve 2, and the wall thickness of the galvanized sleeve 2 is 3mm; the two limbs of the steel strand 3 are arranged crosswise, and the ends of the two limbs are pressed into a pear-shaped anchor head 1 like scattered flowers, and an anchor steel bar 5 is attached to the top of the embossed anchor head 1; the anchor steel bar 5 is spot welded to the steel strand 3; the embossed anchor head 1 is anchored into the interior of the precast concrete component at the same depth.

[0110] Example 5

[0111] A high-strength steel strand prepared in the same manner as in Example 3;

[0112] A high-strength steel strand hanging point, such as Figure 9-10As shown, it includes an embossed anchor head 1, a galvanized sleeve 2, a steel strand 3 and an anchor plate 6; five steel strands 3 are used, the middle part of the steel strand 3 is symmetrically bent 180° to form a hanging ring, the arc section is wrapped with a galvanized sleeve 2, and the wall thickness of the galvanized sleeve 2 is 3mm; the two limbs of the steel strand 3 are parallel U-shaped, and the ends of the two limbs are pressed into a scattered flower-like pear shape from the anchor head 1, and an anchor plate 6 is attached to the top of the embossed anchor head 1; before embossing, the two limbs of the steel strand 3 pass through the reserved holes of the anchor plate 6; the embossed anchor head 1 is anchored in the precast concrete component at the same depth.

[0113] Comparative Example 1

[0114] Example 3 was used as a control group, in which no anti-corrosion layer was prepared and other processes were normal.

[0115] Comparative Example 2

[0116] Example 3 was used as the control group, in which no anti-corrosion layer pretreatment was performed and other processes were normal.

[0117] Comparative Example 3

[0118] Taking Example 3 as the control group, the hexamethylene diisocyanate capsules were replaced with hexamethylene diisocyanate, and the other processes were normal.

[0119] Comparative Example 4

[0120] Example 3 was used as a control group, in which octamethylcyclotetrasiloxane was used to replace the fluorinated vinyl polysiloxane, and the other processes were normal.

[0121] Comparative Example 5

[0122] Example 3 was used as a control group, in which no dopamine hydrochloride solution was added and other processes were normal.

[0123] Source of raw materials used:

[0124] The base material of the steel strand is 1*7-15.2 1860 grade steel strand, which refers to a steel strand with a diameter of 15.2 mm and a prestressed tensile strength of 1860 MPa. 1*7 means that each steel strand has 7 steel wires; formaldehyde, ethanol, zinc nitrate hexahydrate, titanium tetrachloride, dibutyltin dilaurate, analytical grade: Sinopharm Chemical Reagents; petroleum ether P816692, resorcinol R817302, ammonium chloride A801305, trimesic acid T819407, polytetrahydrofuran P816810, sodium dodecylbenzene sulfonate S818303, octamethylcyclotetrasiloxane O823225, polyvinylpyrrolidone P816207, urea U820349, hexamethylenediamine Isocyanate H811014, tris(hydroxymethyl)aminomethane T823912, tetramethylammonium hydroxide T818534, 2,6-diaminopyridine D807016, N,N-dimethylformamide N807505, 1-octanol A867103: Shanghai MacLean Biochemical Technology Co., Ltd.; chloroform PHR1316: Merck reagent; dopamine hydrochloride (99%), biological reagent: Chengdu Grecia Chemical Technology Co., Ltd.; trifluoropropyltrimethylcyclotrisiloxane (D3F), used after drying with 4A molecular sieve: Jinan Langhua Chemical Co., Ltd.; tetramethyltetraenylcyclotetrasiloxane (D4Vi), used after rotary evaporation of water: Shenzhen Ousbang New Materials Co., Ltd.

[0125] Performance test: Performance test of the steel strands obtained in Examples 1-3 and Comparative Examples 1-5:

[0126] Aging resistance: Cut to 150mm in length, first irradiate with xenon arc light with an irradiation energy of 1000MJ / m 2 Keep it for 1000 hours for accelerated aging, and then conduct salt spray test with reference to GB / T 1771-2007, put it into the salt spray box for exposure time of 1500 hours, and the temperature in the box is 35℃;

[0127] Self-healing property: scratches with a depth of 75 μm and a length of 10 μm were made on the coating surface. The damaged sample was kept at 50°C for 12 h, and the healing rate was calculated under a scanning electron microscope.

[0128] Water contact angle: The water contact angle was measured using a contact angle meter; the temperature was 25°C, and a 0.2 μL water droplet was vertically dropped onto the sample surface using the injector, and the average value was obtained after repeating 3 times; the specific data are shown in Table 1;

[0129] Table 1

[0130]

[0131]

[0132] Examples 1-3 are high-strength steel strands prepared according to the present invention. By comparing Example 3 with Comparative Examples 1-5, it can be seen that;

[0133] By comparing Example 3 with Comparative Example 1, it can be seen that when urea is used as the alkali source, by controlling the urea concentration, a dense, complete, and less defective CO3-containing carbon nanotube is generated in situ on the substrate surface. 2- The intercalated zinc-titanium double hydroxide layer achieves chemical repulsion and physical barrier to chloride ions, demonstrating good corrosion resistance.

[0134] By comparing Example 3 with Comparative Example 2, it can be seen that the anti-corrosion layer is treated with trimesic acid and polyvinyl pyrrolidone, that is, a zinc-titanium organic framework is generated in situ on the anti-corrosion layer, thereby enhancing the bonding force with the subsequent organic coating, thereby enhancing the corrosion resistance of the surface of the steel strand; 2,6-diaminopyridine is used as a chain extender and hexamethylene diisocyanate capsules are used as monomers to prepare a polyurethane prepolymer. When the hydrophobic coating is coated on the surface pretreated substrate, the zinc-titanium organic framework is cross-linked with the polyurethane prepolymer to generate a self-healing polyurethane elastomer based on coordination bonds.

[0135] By comparing Example 3 with Comparative Example 3, it can be seen that by optimizing the interfacial polymerization preparation process, the hexamethylene diisocyanate repair agent is encapsulated in the resin capsule wall, and hexamethylene diisocyanate capsules with low particle size are synthesized; when scratches and other crack defects appear on the coating, the microcapsule wall at the scratch position of the coating cracks, and the hexamethylene diisocyanate capsule core self-repairing solution seeps into the scratch defect in large quantities, and a polymerization reaction of the polyurethane self-repairing substance occurs in the water environment, which effectively protects the base metal at the scratch, prevents the development of local corrosion reactions, and produces a synergistic coating self-repairing effect.

[0136] By comparing Example 3 with Comparative Examples 4 and 5, it can be seen that dopamine hydrochloride has a self-polymerization effect, and the introduction of fluorinated vinyl polysiloxane greatly improves the hydrophobicity of the steel strand.

[0137] The above description is only an embodiment of the present invention and does not limit the patent scope of the present invention. All equivalent structural changes made by using the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a high-strength steel strand, characterized in that: The following steps are involved: S1: Wash the base material of the steel strand and dry it for later use; S2: Grind the substrate with sandpaper, prepare anti-corrosion liquid, mix the substrate and anti-corrosion liquid, raise the temperature from 25-30℃ to 115-120℃, keep warm for 22-23h, take out and wash with anhydrous ethanol, dry, and obtain in-situ grown CO3 2- an intercalated zinc-titanium double hydroxide layer, i.e., an anti-corrosion layer; S3: Pretreatment of the anti-corrosion layer: trimesic acid and N,N-dimethylformamide are mixed and stirred, and polyvinyl pyrrolidone and deionized water are added to obtain a pretreatment solution; the substrate having the anti-corrosion layer is immersed in the pretreatment solution, taken out and dried to obtain a substrate with a surface pretreated surface; S4: preparing a hydrophobic coating: in a nitrogen atmosphere, mixing polytetrahydrofuran, hexamethylene diisocyanate capsules, and dibutyltin dilaurate, heating to 80-85°C for 1-2 hours, cooling to 65-70°C, adding 2,6-diaminopyridine and N,N-dimethylformamide, stirring, and drying to obtain a polyurethane prepolymer; mixing a polyurethane prepolymer and chloroform, adding a dopamine hydrochloride solution and a fluorinated vinyl polysiloxane, and stirring to obtain a hydrophobic coating; S5: coating a hydrophobic coating on a surface pretreated substrate, irradiating the substrate with light, forming a hydrophobic layer, and obtaining a high-strength steel strand; The composition of the anti-corrosion liquid is: deionized water as solvent, 0.04 mol / L of zinc nitrate hexahydrate, 0.02 mol / L of titanium tetrachloride, and 0.06 mol / L of urea.

2. The method for preparing a high-strength steel strand according to claim 1, characterized in that: In the pretreatment solution, the mass ratio of trimesic acid to polyvinyl pyrrolidone is 0.1:

2.

3. The method for preparing a high-strength steel strand according to claim 1, characterized in that: The preparation of hexamethylene diisocyanate capsules comprises the following steps: Mix urea and deionized water, add resorcinol, ammonium chloride, deionized water, add sodium dodecylbenzene sulfonate solution, stir for 30-40 minutes, add hexamethylene diisocyanate, continue stirring for 20-30 minutes, add 1-octanol and formaldehyde, ultrasonically disperse in an ice bath environment for 20-30 minutes, heat to 55-60°C and keep warm for 3-4 hours, wash with ethanol and petroleum ether for 5-10 times, filter and dry to obtain hexamethylene diisocyanate capsules.

4. The method for preparing a high-strength steel strand according to claim 1, characterized in that: The working conditions of illumination are: illumination intensity 1kW / m 2 , lighting time 4-5min.

5. The method for preparing a high-strength steel strand according to claim 1, characterized in that: The preparation of dopamine hydrochloride solution comprises the following steps: tris(hydroxymethyl)aminomethane, dopamine hydrochloride and deionized water are mixed and stirred, and the pH value is adjusted to 8.4-8.7 to obtain the dopamine hydrochloride solution.

6. The method for preparing a high-strength steel strand according to claim 1, characterized in that: The preparation of fluorine-containing vinyl polysiloxane comprises the following steps: in a nitrogen atmosphere, octamethylcyclotetrasiloxane, trifluoropropyltrimethylcyclotrisiloxane and tetramethyltetraenylcyclotetrasiloxane are mixed, and the mixture is heated to 85-90° C. and kept warm for 20-30 minutes; the mixture is heated to 105-110° C., an aqueous solution of tetramethylammonium hydroxide is added, deionized water is added, and the mixture is kept warm for 2-3 hours; the mixture is heated to 145-150° C. and kept warm for 2 hours, and the pressure is reduced for 3 hours to obtain fluorine-containing vinyl polysiloxane.

7. A high-strength steel strand, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. A high-strength steel strand hanging point, characterized in that: The high-strength steel strand is prepared from the high-strength steel strand described in claim 7, and the production comprises the following steps: 1) Cut the steel strand (3) and the galvanized casing (2) to the designed length; 2) Sleeve the galvanized sleeve (2) onto the middle section of the steel strand (3) and bend it into shape; 3) When adding spiral stirrups (4) or anchor plates (6), pass the two ends of the steel strand (3) through the positioning holes on the spiral stirrups (4) or anchor plates (6), and press the two ends of the steel strand (3) into a pear-shaped self-anchor head with scattered flowers; 4) When a plurality of steel strands (3) are used, the steel strands (3) are arranged into groups; when anchoring steel bars (5) are added, the anchoring steel bars (5) and the steel strands (3) are spot welded; 5) The high-strength steel strand hanging point is placed in the prefabricated component reinforcement cage for fixing, and when the anchor reinforcement (5) is attached, the anchor reinforcement (5) is spot welded to the reinforcement cage; 6) Pour concrete for precast components and complete the production of hanging points.

9. A high-strength steel strand hanging point according to claim 8, characterized in that: 2) The bending angle of the medium steel strand is one of 120°, 150° and 180°.

Citation Information

Patent Citations

  • Anti-corrosion aluminum-clad steel stranded wire and production method thereof

    CN111009350A

  • High-strength tensile galvanized steel strand

    CN212152917U